Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai Badan Penghubung Provinsi Maluku - Jihan; Murniyati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Leadership style and work environment are two important factors that influence employee performance, especially in government agencies such as the Maluku Provincial Liaison Agency. This study aims to determine the effect of leadership style and work environment on employee performance. The method used is a quantitative approach by distributing questionnaires to 45 respondents who are all employees of the Maluku Provincial Liaison Agency. Data collection techniques were carried out through observation, interviews, questionnaires, and literature studies. Data analysis was carried out using SPSS version 27 software, with validity, reliability, classical assumptions, multiple linear regression, and determination coefficient tests. The results of the T test showed that leadership style did not have a significant effect partially (sig. 0.078 > 0.05), while the work environment had a significant effect (sig. 0.001 < 0.05). The F test showed that simultaneously both variables had a significant effect on employee performance (sig. 0.001 < 0.05). These findings imply that improving employee performance can be achieved through the creation of a more conducive work environment, as well as a communicative and supportive leadership style.